“Iran’s Shiite Influence Belt Policy: The Example of Bahraini Shiites - Orhan Karaoğlu (Dini Araştırmalar, 2022)

(untitled)
Along with the Persian perspective inherited from the Persian Empire, Shi'ism has significantly influenced and continues to influence the geopolitical and geo-cultural education of present-day Iran. With its politicization, Shi'ism has become one of the most important factors, perhaps the most important, in the formation and preservation of Iran's national identity. Iran, which is in contact with Shiites living in various regions such as Middle East-Africa-Central Asia, intensified this contact after the Arab Spring process. In this article, Shiites in Bahrain are discussed in the context of Iran's Shiite Influence Zone Policy. In the article, firstly, general information about the sociological and religious structure of Bahrain has been given, and then the characteristics of the Shiite groups and leaders in Bahrain have been mentioned. Then, the level and activities of these groups' relations with Iran, the Shiite militia groups, their characteristics, and their work on behalf of Iran are discussed. The research has carried out based on the literature review.